EFEKTIVITAS MODEL PROJECT-BASED LEARNING BERBASIS LINGKUNGAN SEKITAR DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA KELAS V - Muhammad Khidayatullah Irfan; Dewi Fitriani; Siti Maisarah; Hendra Kurniawan; Firda Weri; Nada Ayu Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science education at the elementary school level is essential for fostering scientific thinking patterns and developing 21st-century skills, including science process skills (SPS). However, prior studies indicate that students’ SPS particularly in Muara Bulian District, Jambi remain at a low level due to the predominant use of lecture-based methods and the limited opportunities for scientific exploration. This study aims to evaluate the effectiveness of a Project-Based Learning (PjBL) model based on the local environment in improving the SPS of fifth-grade students at SDN 34/1 Teratai, Muara Bulian. The research employed a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group. The results show a significant improvement in the experimental group’s average SPS scores, increasing from 62.40 to 85.70 with a gain score of 0.63 (moderate category). Meanwhile, the control group’s scores increased from 61.80 to 73.40 with a gain score of 0.38 (low category). The enhancement was observed across all SPS indicators, including observing, classifying, interpreting, designing experiments, and communicating. These findings suggest that the environment-based PjBL model is effective in enhancing students’ SPS and contributes to a more contextual, active, and meaningful science learning experience. Therefore, this model can serve as an alternative strategy to improve the quality of physics and science education at the elementary level.